The Unborn Child: History, Philosophy and Religion - LUCAN, Maria Casandra (Journal of Legal Studies, 2017)
All throughout history the unborn, and implicitly its protection, have been subject for academics and practitioners of various areas. The problem of the origin of the soul and the exact determination of the moment when it is united with the body was crucial in enabling us to define the exact moment when the human life begins, and, consequently, for providing proper protection for the unborn child. In this context visions of the Greek philosophers like Plato, Aristotle, Albertus Magnus and Thomas Aquinas, and of the Latin writer Tertullian, as well as Christian perspectives were analysed in order to identify the starting point of the human being to help determine the level of protection provided for the unborn in history. Finally, considering the fact that not even today has consensus been achieved concerning the beginning of human life, it was and still is difficult to provide proper legal protection for the unborn child, but in our opinion this is by far not impossible.